Parkinson's disease pathology is directly correlated to SIRT3 in human subjects and animal models: Implications for AAV.SIRT3-myc as a disease-modifying therapy - Trinh, Dennison; Israwi, Ahmad R.; Brar, Harsimar; Villafuerte, Jose E.A.; Laylo, Ruella; Patel, Humaiyra; Jafri, Sabika; Al Halabi, Lina; Sinnathurai, Shaumia; Reehal, Kiran; Shi, Alyssa; Gnanamanogaran, Vayisnavei; et al. (Neurobiology of disease, 2023)
In Parkinson's disease (PD), post-mortem studies in affected brain regions have demonstrated a decline in mitochondrial number and function. This combined with many studies in cell and animal models suggest that mitochondrial dysfunction is central to PD pathology. We and others have shown that the mitochondrial protein deacetylase, SIRT3, has neurorestorative effects in PD models. In this study, to determine whether there is a link between PD pathology and SIRT3, we analysed SIRT3 levels in human subjects with PD, and compared to age-matched controls. In the SNc of PD subjects, SIRT3 was reduced by 56.8 ± 15.5% compared to control, regardless of age (p < 0.05, R = 0.6539). Given that age is the primary risk factor for PD, this finding suggests that reduced SIRT3 may contribute to PD pathology. Next, we measured whether there was a correlation between α-synuclein and SIRT3. In a parallel study, we assessed the disease-modifying potential of SIRT3 over-expression in a seeding model of α-synuclein. In PFF rats, infusion of rAAV1.SIRT3-myc reduced abundance of α-synuclein inclusions by 30.1 ± 18.5%. This was not observed when deacetylation deficient SIRT3H248Y was transduced, demonstrating the importance of SIRT3 deacetylation in reducing α-synuclein aggregation. These studies confirm that there is a clear difference in SIRT3 levels in subjects with PD compared to age-matched controls, suggesting a link between SIRT3 and the progression of PD. We also demonstrate that over-expression of SIRT3 reduces α-synuclein aggregation, further validating AAV.SIRT3-myc as a potential disease-modifying solution for PD. [Display omitted] •SIRT3 is negatively correlated with age and Parkinson's disease pathology in humans.•In rats, pre-formed fibrils (PFF) of α-synuclein cause dopaminergic cell loss and dysfunction of dopamine metabolism.•Pathological α-synuclein accumulates in the substantia nigra pars compacta and other brain regions of PFF-infused rats.•Over-expression of SIRT3 reduces pathological α-synuclein aggregation.•SIRT3 may provide disease-modifying effects for Parkinson's disease patients.